VALUE LIFE EDUCATIONS ANAK USIA DINI BERBASIS CERITA BERGAMBAR DI TK NEGERI 1 SINTANG - Mulyadi, Yohanes Berkhmas; Suryameng, Suryameng; Sarayati, Sarayati (STKIP Persada Khatulistiwa Sintang, 2024)
This research starts from the fact that there are still children who are impolite, like to lie, make noise in class, and come late to school. In fact, at an early age, children are accustomed to receiving superior values such as ethics, morals and discipline. This research aims to describe the value of early childhood education based on picture stories at TK Negeri 1 Sintang. This research applied descriptiveÂ research with a qualitative approach. The research subjects were determined using a purposive sampling technique. The research subjects consisted of teachers and studentsâ€™ parents of TK Negeri 1 Sintang. Data collection in this research was carried out by observation, in-depth interviews and documentation. Data analysis techniques involved data reduction, categorization, display/presentation and drawing conclusions. The results of the research show that teachers and parents really need their role in educating, guiding, applying life values to children, getting children accustomed to living life values so that in the future these values are internalized in children. The implementation of value life education in TK Negeri 1 Sintang includes religious values, responsibility, cooperation, discipline, care, appreciation, joy and patience. The obstacles in implementing value life education is that parents have not been able to support students' life value education at home because there are still parents who do not apply these life values because they are busy on working. Although some are as expected. Teachers play a very important role in supporting this program because teachers are examples, but as ordinary people, teachers sometimes lack of patience to educate children.